Leptochilus oblongus (Polypodiaceae), a new fern species from northern Vietnam - Zhang, Liang; Lu, Ngan Thi; Zhang, Li-Bing (Phytotaxa, 2015)
A new fern species, Leptochilus oblongus of Polypodiaceae is described and illustrated from Hoa Binh Province, northern Vietnam. Leptochilus oblongus is most similar to L. ellipticus, but the sori of the former are oblong, close to the lobe margins, and parallel with costule. In contrast, those of the latter are linear, located on main lateral veins, and forming a ca. 45 degree angle with costule.